Relación entre reforma pensional 2024 y el antiguo régimen (ley 100 de 1993), implicaciones y posibles escenarios (2025)
Colombia's Law 100 of 1993, also known as the Comprehensive Social Security Law, introduced significant changes to the country's social security system, especially in the health and pension sectors. This legislation established the basis for the creation of the Pension Fund Administrators (AFP), which is the case to be analyzed specifically, with the aim of guaranteeing pension coverage for the Colombian population. But over the years it has been facing a series of criticisms and modifications by different government periods. But in this case we are going to analyze the approach of the new 2024 pension reform that will come into force as of June 2025 and that brings with it a series of questions and perspectives that become an unknown for people affiliated with both the private and public system.